Analisis Proses Rekrutmen dan Seleksi pada Kinerja Pegawai - YULLYANTI, ELLYTA (UI Scholars Hub, 2011)
The purpose of this research is to explain whether any impact of recruitment to the selection, the recruitment impact to the performance and selection impact to the performance of employee of the General Secretariat of Department of Energy and Mineral Resources. The approach which has been used in this research is descriptive and data processing by using Structural Equation Modeling (SEM) Technique. The sample of this research is 120 employees. The result of this research shows that selection significantly is affected by recruitment and so that the performance is significantly affected by selection, however, recruitment is indirectly affected the performance by selection process.